Pengaruh Corporate Social Responsibility dan Struktur Modal Terhadap Nilai Perusahaan - Sutriningsih Sutriningsih; Eti Susanti (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of corporate social responsibility and capital structure on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the 2015–2017 period. This study uses a quantitative approach with a causality research type. The data used are secondary data obtained from annual reports and company financial statements, collected through documentation techniques. The study population includes all manufacturing companies listed on the Indonesia Stock Exchange, with the sample determined using a purposive sampling technique, resulting in 108 sample units that meet the research criteria. Data analysis was conducted using multiple linear regression to test the influence of independent variables on the dependent variable. The results of the study indicate that corporate social responsibility disclosure has a positive and significant effect on firm value, as well as capital structure, which is proven to have a significant effect on firm value. These findings provide an empirical contribution in strengthening evidence that non-financial policies, particularly corporate social responsibility disclosure, along with appropriate funding structure management, play an important role in increasing market perception of firm value. The results of this study are expected to be a consideration for company management in formulating strategic policies oriented towards increasing firm value in a sustainable manner.